2011
DOI: 10.1007/s10458-010-9165-y
|View full text |Cite
|
Sign up to set email alerts
|

AutoMed: an automated mediator for multi-issue bilateral negotiations

Abstract: In this paper, we present AutoMed, an automated mediator for multi-issue bilateral negotiation under time constraints. AutoMed elicits the negotiators preferences and analyzes them. It monitors the negotiations and proposes possible solutions for resolving the conflict. We conducted experiments in a simulated environment. The results show that negotiations mediated by AutoMed are concluded significantly faster than non-mediated ones and without any of the negotiators opting out. Furthermore, the subjects in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…This uncertainty was also shared by the mediator, that had information solely on the preference relation between the issues and values under negotiation. AniMed significantly increased the individual utility score and the social welfare, measured by the sum of utilities, of both negotiators, compared to experiments in which another state-of-the-art mediator [3] or no mediator were involved. The results also indicate that while people are content with the solutions they achieve without any mediator involved, better solutions can be achieved when AniMed is present.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…This uncertainty was also shared by the mediator, that had information solely on the preference relation between the issues and values under negotiation. AniMed significantly increased the individual utility score and the social welfare, measured by the sum of utilities, of both negotiators, compared to experiments in which another state-of-the-art mediator [3] or no mediator were involved. The results also indicate that while people are content with the solutions they achieve without any mediator involved, better solutions can be achieved when AniMed is present.…”
Section: Introductionmentioning
confidence: 89%
“…One experiment involved matching people without any mediator. In another experiment we matched two people with a simple automated mediator, AutoMed, suggested by Chalamish and Kraus [3]. They demonstrated that this mediator enables the negotiators to achieve more satisfactory solutions in environments where only messages are exchanged.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, there is a growing literature focused on optimally managing negotiations between strategic, self-interested agents (Brafman & Tennenholtz, 1996;Chalamish & Kraus, 2012;Lopez-Carmona, Marsa-Maestre, Klein, & Ito, 2012). The primary difference between our paper and the current literature is that our bargaining game is unstructured, while the others use a structured game.…”
Section: Contribution Of This Papermentioning
confidence: 98%
“…Within the field of artificial intelligence (AI), there is an active effort of research for studying negotiation processes using agent based modeling [20] and developing support tools for mediation [5]. These, together with the recent formulation of a mediation framework by Simoff et al [32], provide a theoretical basis for a computational approach to mediation, which can promisingly address the aspects mentioned above.…”
mentioning
confidence: 99%